2005
DOI: 10.1016/j.curtheres.2005.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-related adverse effects impacting treatment compliance: Results of a patient survey

Abstract: The findings of this survey of patients with mild to severe10 depression suggest that compliance, and hence efficacy, can be promoted by (1) understanding what patients expect and desire from the antidepressants they are prescribed and (2) prescribing antidepressants associated with low rates of weight gain, sexual dysfunction, or tiredness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 10 publications
0
76
1
Order By: Relevance
“…Cross sectional population survey also reveal that sexual problems among men were associated with anxiety and medical problems, whereas for women sexual dysfunction was associated with marital difficulties. Studies evaluating the marital relationship have shown that marital satisfaction was significantly associated with sexual desire [45]. Other researchers consider marital distress as a causal determinant and as an outcome of low sexual desire; low marital satisfaction can reduce motivation for sexual intimacy and perhaps even promote sexual withholding, and lack of sexual desire over time can lead to frustration and dissatisfaction.…”
Section: Impact Of Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross sectional population survey also reveal that sexual problems among men were associated with anxiety and medical problems, whereas for women sexual dysfunction was associated with marital difficulties. Studies evaluating the marital relationship have shown that marital satisfaction was significantly associated with sexual desire [45]. Other researchers consider marital distress as a causal determinant and as an outcome of low sexual desire; low marital satisfaction can reduce motivation for sexual intimacy and perhaps even promote sexual withholding, and lack of sexual desire over time can lead to frustration and dissatisfaction.…”
Section: Impact Of Sexual Dysfunctionmentioning
confidence: 99%
“…One of the important consequences of sexual dysfunction in people taking antidepressants is poor treatment acceptance and compliance [45]. Studies have shown that sexual dysfunction is the 2nd most frequent side effect rated as "extremely difficult to live with" after weight gain and 3rd most frequently reported side effect as a cause of noncompliance [47].…”
Section: Impact Of Sexual Dysfunction On Compliancementioning
confidence: 99%
“…While SSRIs and TCAs are similarly effective [33], SSRIs are prescribed more often because of their favourable side-effect profile [34]. Rates of antidepressant treatment discontinuation can reach up to 60 per cent, and adverse effects are the most common reason for nonadherence and drug discontinuation [35]. Fifteen to twenty-seven per cent of patients discontinue medication use owing to perceived side effects [36].…”
Section: Nocebo Effects In Antidepressant Trialsmentioning
confidence: 99%
“…The most common reasons were forgetfulness (43 per cent), sexual dysfunction (40 per cent), weight gain (27 per cent) and daytime drowsiness (21 per cent). 23 Side-effects such as nausea, headache, drowsiness and increased anxiety are common reasons why 43 per cent to 62 per cent of patients stop taking both old and the newer antidepressants. 9,24 In patients in maintenance phase treatment with antidepressants, compliance was lowest when perceived harm exceeded perceived need and highest when perceived need exceeded concerns about taking the medication.…”
Section: Why Do Patients Not Take Their Antidepressants As Prescribed?mentioning
confidence: 99%